An empirical study of auditors’ efforts, audit technology and impact on tax auditors’ performance - Ahmad, Mohmad Hazar; Mustapha, Mazlina; Yusri, Yusniyati; Kharuddin, Saira (Penerbit Universiti Kebangsaan Malaysia, 2024)
The tax auditors’ performance is crucial in determining the success of tax audit implementations conducted by tax administrators. This study explores how auditors’ efforts and audit technology influence tax auditors’ performance in the Malaysian context. The objective is to examine the influence of internal factors, such as auditors’ effort and external factors, such as audit technology, on tax auditors’ performance based on the attribution theory. Based on a quantitative approach, this research utilized survey questionnaires distributed to tax auditors ranked in executive level and above, with at least one year of tax audit experience from the Inland Revenue Board of Malaysia and the Royal Malaysian Customs Department, which handle direct and indirect taxes. The Structural Equation Modelling (SEM) was utilized for data analysis, revealing a significant and positive correlation between auditors’ efforts, audit technology and tax auditors’ performance. This study provides valuable insights for policymakers by identifying key factors that influence audit effectiveness and the performance of tax auditors. These findings can inform the development of targeted policies aimed at enhancing tax compliance and strengthening regulatory frameworks. Ultimately, this research serves as a vital resource for both practitioners and scholars interested in understanding and improving the effectiveness of tax audits within an evolving economic landscape.